IoT integrated conveyor centralized system - Abu Zaki, Zahirah; Abd Kadir Mahamad, Abd Kadir Mahamad; Sharifah Saon, Sharifah Saon; Othman, Maisara; Elmunsyah, Hakkun; Ahmadon, Mohd Anuaruddin; Shingo Yamaguchi, Shingo Yamaguchi (2024)
This research introduces Factory I/O, Modbus TCP/IP, and Node-RED technology to enhance industrial material distribution systems by incorporating visual sensors for efficient object segregation on conveyor belts. The objective is to expedite and enhance precision in item separation based on color, optimizing overall productivity. The implementation includes a local supervision technique for comprehensive control, ensuring a dependable and efficient system. Factory I/O simulation software analyzes the conveyor system's efficiency with vision sensors, providing a virtual environment for mock testing. Node-RED facilitates real-time data visualization and analysis, improving control and monitoring capabilities. The UI dashboard offers immediate insight into Overall Equipment Effectiveness (OEE) for efficient decision-making. This research significantly contributes to automated material handling in production through enhanced efficiency and comprehensive process overview in automation and vision-based sensor segregation.